Aging-associated and CD4 T-cell-dependent ectopic CXCL13 activation predisposes to anti-PD-1 therapy-induced adverse events - Tsukamoto, Hirotake; Komohara, Yoshihiro; Tomita, Yusuke; Miura, Yuji; Motoshima, Takanobu; Imamura, Kosuke; Kimura, Toshiki; Ikeda, Tokunori; Fujiwara, Yukio; Yano, Hiromu; Kamba, Tomomi; Sakagami, Takuro; et al. (Proceedings of the National Academy of Sciences - PNAS, 2022)
Clinical success of immune-checkpoint blockade (ICB) cancer immunotherapy is compromised by increased risk of immune-related adverse events (irAEs). However, mechanistic action(s) of immune responses underlying development of irAE remain not fully explored. Here, we found that in tumor-bearing aged, but not young, mice, antiprogrammed death receptor (PD)-1 therapy elicited irAE-like multiorgan dysfunctions with ectopic accumulation of T and B cells in damaged organs. In this preclinical model, the organ toxicities were mediated by immunoglobulin G (IgG) deposition because administration of IG from ICB-treated aged mice induced the pathogenicity specifically in naïve aged hosts. Mechanistically, CD4 T-cell-derived interleukin (IL)-21 upregulated B-cell-homing chemokine, CXCL13, preferentially in irAE organs from aged mice treated with anti-PD-1 therapy. The ICB-induced pathogenicity was alleviated by B-cell depletion or by blockade of IL-21 or CXCL13 activity. These results suggest that age-associated immune regulatory milieu contributes to the formation of tertiary lymphoid structure-like lymphocytic aggregates in irAE organs and irAE-related toxicity employing IL-21-CXCL13-auto-antibody axis. Supporting this, a systemic increase in CXCL13 and expression in CD4 T cells correlated with irAE incidence in ICB-treated patients. These findings provide rationale for therapeutic usefulness of CXCL13 in irAE management.